Composition of Functions

Composition of Functions

Composition of Functions Definition: ForMath functions 140 f andLectureg, define 6f ◦ g, the compositionWriteof f andeachg functionby, below as a composition Study Practice Exam 1 and the recommended(f ◦ exercises.g)(x) = f (g(x)) f (g(x)) of two simpler functions, Functions can be added and multiplied just like numbers. an outer function f and an inner function g. DEFINITION. For functions f, g, define f +g, f - g, f.g, f /g Find the inner function first. by Dom(f ◦ g) = fx 2 dom(g)jg(x) 2 dom(f)g `Write x2 26 as a composition fgx. (f + g)(x) = f (x) +g(x), Note: (f +g)(x) is not (f +g).(x) Example: Suppose f(x) = x − 2 and g(x) = x2. x2 26 inner function gxx2 2 (f - g)(x)= f (x)- g(x), The first is function application. (fg)(x) = f (x)g(x), The second is multiplication. „ outer function fx does what remains (a) Find (f ◦ g) and (g ◦ f). 6 (f /g)(x) = f (x)/g(x). x to be done. t fxx6. `If f (x) = x- 2, g(x) = 6, then 2 2 (f ◦ g)(x) = f(g(x)) = f(x ) = x − 2 check: fgx f x2 2x2 26. (f + g)(x) = f (x) + g(x) = (x- 2) + (6) = x + 4, 2 2 1 (f-g)(x()g =◦ f ()(xx) )- = g(gx()f (=x ))(x =- 2)g(x -− (6)2) = = x ( x- −8,2) = x − 4x + 4`Write 4 x 3 as a composition f gx. 1 1 (fg)(***Note:x) = f (x)g((fx)◦ =g )(6=x- (2)(6)g ◦ f) = 6x-12, 4 x 3 inner function gx x 1 1 (f /g)(x) = f (x)/g(x) = (x-2)/6 = 6 x 3 . „ outer function f x does what remains DEFINITION(b) Find. For (f functions◦ g)(2) and f and (g ◦ gf,)(2). define fog, the 4x 3 to be done. t composition of f and g, by f x4x 3. (f ◦ g)(2) = f(g(2)) = f(22) = f(4) = 4 − 2 = 2 1 1 (fog)(x) = f (g(x)) check: fgx f x 4 x 3. 2 Apply g to(g ◦x.f Get)(2) g =(xg).(f Apply(2)) = gf(2 to− g2)(x =). gGet(0) f = (g 0(x=)). 0 `Write x 1 as a composition. f is the outer function; g is the inner function. x 1 Example: For f(x) = 3x + 4 and 2g(x) = 5, find (f ◦ g) and (g ◦ f). `Suppose f (x) = x-2 and g(x) = x . „ gxx 1 (a) Find f(ofg◦ andg)(x g)o =f. f(g(x)) = f(5) = 3(5) + 4 = 19 2 2 x f x x (fog)(x) = f(g(x)) = f (x ) = x -2. 2 2 check: f gx f x 1 x 1 . (gof)(x) (=g g◦(f(x)())x )= =g(xg-2)(3x =+ (x 4)-2) = = 5 x - 4x + 4. Note that f og = gof. For composition, order matters. `Write x4 x2 1 as a composition. (b) Example:Find (fog)(2).For f and g below, note that x4 x2 1 x22 x21. 2 2 Since (fofg(−)(x3)) = = x 1,-2,f ((f−og1))(2) = = 2, 2f-2(2) = =4-2 3, =f 2.(4) = 2, and 2 g(−2) = −1, g(−1) = −2, g(1) = −1, g(2) = 2. gxx (b’) Find (fog)(2) and (gof )(2) directly without (fog)(x), 2 Find: f xx x 1 (gof )(x). 2 4 2 (fog)(2) = f(g(2)) = f(22) = f(4) = 4-2 = 2. check: f gx fx x x 1. 2 (gof)(2)( =f g(f(2))◦ g)(2) = = g(2-2)f(g(2)) = g(0) = f =(2) 0 == 0. 3, `Write x /1 x as a composition of 2 functions. 2 `Write as a composition of 3 functions. `If h(x) = c, then h(8) = c, h(y) = c, h(x -1) = c, h(g(x)) = c. 1/1 |x| (g ◦ f)(2) = g(f(2)) = g(3) = undefined, Ans hfgx, gx|x|, fx1 x, hx1/x `For f (x) = 3x+4, g(x) = 5, find fog and gof. f(g(x)) = f(5) = 3.5+4 = 19. g(f(x)) =( fg(3◦ xf+4))(− =1) 5. = f(f(−1)) = f(2) = 3 DEFINITION. id(x) = x is called the identity function. id(x)=x f(x) g(x) 2 2 Hence id(5) = 5, id(y) = y, id(x -1) = x -1, ... For f and g above, note that THEOREM. For any function f (x), foid = f and idof = f. f(-3) = 1, f(-1) = 2, f(2) = 3, f(4) = 2, and PROOF. ( foid)(x) = f (id(x)) = f (x). g(-2) = -1, g(-1) = -2, g(1) = -1, g(2) = 2. (idof )(x) = id(f (x)) = f (x). Find 0 is the identity for addition, since f + 0 = 0 + f = f . (fog)(2) = f(g(2)) = f(2) = 3. 1 (gof)(2) = g(f(2)) = g(3) = undef. 1 is the identity for muliplication, f .1 = 1. f = f . (fof)(-1) = f(f(-1)) = f(2) = 3. id(x) is the identity for composition, since 1 1 1 1 x `fxx x , ffx x x 1/x x x x x21 foid = idof = f . 1 Example: f(x) = x + x . Find (f ◦ f). 1 1 1 x (f ◦ f)(x) = f(f(x)) = (x + x ) + ( 1 ) = x + x + x2+1 x+ x Next we want to write a function as a composition of 2 simpler functions. Example: Write (x2 + 2)6 as a composition f(g(x)). (x2 + 2)6 has an inner function g(x) = x2 + 2. Then the outer function f(x) does what remains to be done: f(x) = x6. Check: f(g(x)) = f(x2 + 2) = (x2 + 2)6. 1 Example: Write 4 x + 3 as a composition f(g(x)). 1 1 4( x ) + 3 as inner function g(x) = x . Then the outer function f(x) does what remains to be done: f(x) = 4x + 3. 1 1 Check: f(g(x)) = f( x ) = 4( x ) + 3. p Example: Write x + 1 as a composition f(g(x)). p x + 1 has inner function g(x) = x + 1 p So f(x) = x. p Check: f(g(x)) = f(x + 1) = x + 1. Example: Write x4 + x2 + 1 as a composition. x4 + x2 + 1 = (x2)2 + x2 + 1. ) g(x) = x2 ) f(x) = x2 + x + 1. Check: f(g(x)) = f(x2) = (x2)2 + x2 + 2 = x4 + x2 + 1. 1 Example: Write 1+jxj as the composition of 3 functions h(f(g(x))). 1 1+jxj has inner function g(x) = jxj 1 (1+x) has inner function f(x) = 1 + x 1 Thus h(x) = x . 1 Check: h(f(g(x))) = h(f(jxj)) = h(1 + jxj) = 1+jxj 2 -1 `If f (x) = x+3 then f (-1x) = x-3. Math 140 Lecture 7 `If f (x) = x+3 then f (x) = x-3. Math 140 Lecture 7 -1 If g(x) = x/2 then g (-1x) = 2x. Inverse functions If g(x) = x/2 then g (x) = 2x. Inverse functions -1 2 -1 If h(x) = x then h (-1x) = x for2 x > 0. DEFINITION. f ,-1 the inverse of f , is the function, if any, If h(x) = x then h (x) = x for x > 0. DEFINITION. f , the inverse of f , is the function, if any, -1 Note how the graph of f is related to the graph of f .-1 such that, such that, Note how the graph of f is related to the graph of f . -1 -1 f ( f (-1x)) = x when f (-1x) is defined and -1 f ( f (x)) = x when f (x) is defined and g -1 -1 g h f (-1 f (x)) = x when f (x) is defined. h f ( f (x)) = x when f (x) is defined. g -1-1 g -1 -1 f f -1 This says that f and f -1undo each other: f f h This says that f and f undo each other: h -1 f -1undoes what f (x) does and gives you back x. f undoes what f (x) does and gives you back x. -1 -1 -1 `f(x) =2x, f (-1x)=½x. Verify: f(f (-1x))=x & f ( -1f (x))=x `f (x) = 2x, f (x) = ½x. Verify: f (f (x)) = x & f (f (x)) = x -1 -1 `g(x) = x +3, g (-1x) = x-3. By the Theorem, y = f (-1x) iff f (y) = x. Thus the graph of `g(x) = x +3, g (x) = x-3. By the Theorem, y = f (x) iff f (y) = x. Thus the graph of -1 1 3 -1 `h(x) = 2x +3, h (-1x) = (x-3)/2 = x1 .3 y = f (-1x) is the graph of f (y) = x which is just the graph `h(x) = 2x +3, h (x) = (x-3)/2 =2 x 2 . y = f (x) is the graph of f (y) = x which is just the graph -1 2 2 Verify that h (-1h(x)) = x. of f (x) = y with x and y interchanged. Interchanging x Verify that h (h(x)) = x. of f (x) = y with x and y interchanged. Interchanging x To undo a sequence of operations, you must undo them in and y reflects the plane around the major diagonal y = x. To undo a sequence of operations, you must undo them in and y reflects the plane around the major diagonal y = x.

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    4 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us